REFORMULASI DELIK MAKAR DALAM RANCANGAN KITAB UNDANGUNDANG HUKUM PIDANA NASIONAL TAHUN 2019 (SEBUAH TELAAH LEKSIKAL TERHADAP TERMINOLOGI AANSLAG) - Fajrin, Yaris Adhial (Jurnal Hukum & Pembangunan, 2021)
The use of the term Makar as a translation of the word Aanslag in Indonesias CRIMINAL code currently triggers a variety of polemic because it has a lot of meaning, resulting in an ambiguity that causes no legal certainty to be guaranteed. Indonesias CRIMINAL code is currently in its case that it does not provide define and the limitations of Macar deeds so that the multitasking is still prone to occur. Addressing such a thing, it is necessary to reformulation the draft proceeding in the Penal Code in order to ensure the future legal certainty. The limitation of the performance of at least should contain intention, commencement, and physical or nonphysical attack